Wyndham Lewis - ‘War’ as a new subject-matter for Art - Veloso, Manuela (Cadernos de Literatura Comparada, 2014)
It is interesting to observe that Vorticism has the same duration as the First World War: Blast 1 was launched in 1914 and faded out in 1918, after the Vorticist exhibition in New York, in 1917. «Super-Krupp – or the War’s End» (Blast 2) is an essay that focuses the war subject, in which Wyndham Lewis evidences what his opinion is: “As to Desirability, nobody but Marinetti, the Kaiser, and professional soldiers WANT War. And from that little list the Kaiser might have to be extracted” (Lewis, 1915: 14). His attitude, both as an artist and as an individual beyond a civilization, leads him to assert, in the manifesto “The Art and the Race”, that the universality of an artist walks on the ground of detachment from circumstantialities, in order to become a unique being integrating humanity. The enthusiasm (or blast) to search for a synthesis of all the arts that would result in a very desirable power counterforce was a credo of the avant-garde movements in Europe, and German Expressionism is not an exception. Avant-garde German and British soldier-artists were eventually at war with the same ontological status quo, in spite of having been in opposite trenches in the Front. In the case of Lewis writing and pictorial production from its inception to his final period – with a major focus on the First World War and the interwar period – satire has always been “the great Heaven of ideas” (Men without Art).